Pengaruh Implementasi Literasi Berbasis Digital Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Di Sma Ma’arif Nu Pandaan - Ira Dwiyanti; Muhammad Abdullah; M. Jumhuri; Ahmad Ma'ruf (Ulumuna: Jurnal Studi Keilsman, 2023)
His research entitled "The Effect of Digital Based Literation Performances towards Pupils' Achievements on Akidah Akhlak in SMA Ma'arif NU Pandaan". The aim of this research is to apprehend The Effect of Digital Based Literation Performances towards Pupils' Achievements on Akidah Akhlak. This reserach used a qualitative method with Simple Linier Regression. The data of this research was acquired through observations and questionnaires towards 70 samples of 239 population using Purposive Sampling. The result of this research explains that there is a significant outcome towards pupils' learning development which is showed by Pearson Product Moment Correlation. The result of the correlation is 3.401, meanwhile the X variable of the Cronbach Alpha is 0,675 and the Y variable is 0.802.